Natural product manoalide promotes EGFR-TKI sensitivity of lung cancer cells by KRAS-ERK pathway and mitochondrial Ca2+ overload-induced ferroptosis - Ni, Yinyun; Liu, Jiaye; Zeng, Lingyan; Yang, Ying; Liu, Lei; Yao, Menglin; Chai, Li; Zhang, Lu; Li, Yi; Zhang, Li; Li, Weimin (Frontiers in Pharmacology, 2023)
Manoalide (MA), a proven natural inhibitor of PLA2 has anticancer effects, but its potential application and mechanism as an anticancer drug to promote EGFR-TKI sensitivity in lung cancer cells have not been studied. In this study, we found that MA inhibited the proliferation of KRAS-mutated lung cancer cells and organoids. Subsequently, we demonstrated that MA induced ER stress via oxidative stress. In addition, the ROS induced by MA is mainly in mitochondrial and causes lipid peroxidation, thereby inhibiting mitochondrial fatty acid oxidation metabolism and promoting the accumulation of lipid droplets. We further demonstrated that MA inhibited the KRAS-ERK pathway through a ROS-dependent mechanism and promoted the sensitivity of KRAS-mutated lung cancer cells and organoids to osimertinib. Furthermore, we found that MA induces ferroptosis via suppressing the NRF2-SLC7A11 axis and mitochondrial Ca2+ overload induced-FTH1 pathways to promote the sensitivity of osimertinib-resistant lung cancer cells to osimertinib. Taken together, our data suggest that the natural product MA is a new EGFR-TKI sensitizer in KRAS-mutated and osimertinib-resistant lung cancer cells.